Study of the Weeb Simp Phenomenon in VTuber Using the Uses and Gratifications Theory: Studi Fenomena Weeb Simp pada VTuber dengan Teori Uses and Gratifications - Maulana, Muhammad Rizky; Dharma, Ferry Adhi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rise of virtual YouTubers (VTubers) represents a significant development in digital entertainment, creating a new space for audience interaction and community formation. Specific Background: The phenomenon of